Pneumonectomy for Benign Lung Disease: Peshawar Experience of 320 Cases (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the surgical outcome of pneumonectomy for benign lung disease. Study Design: Retrospective observational study. Place and Duration of study: Cardiothoracic Surgery Unit, Post Graduate Medical Institute, Lady Reading Hospital, Peshawar, from June 2002 to December 2011. Material and Methods: Computerized clinical record of 320 patients who underwent pneumonectomy for benign lung diseases from June 2002 to December 2011 was retrospectively analyzed carefully for surgical outcome. Patient of all ages, both sexes and diagnosed benign lung parenchymal diseases were included. Patient with bilateral parenchymal disease, pneumonectomy for malignancy and trauma and medically unfit patients were excluded from the study. All patients were admitted through outpatient department as a referral or shifted from pulmonology and medical units. Routine workup include all baseline blood investigations, sputum for AFB, X-ray chest, CT scan chest with I/V contrast, pulmonary function test, echocardiography in elderly patients, exercise testing in patients with marginal pulmonary function test. Except for smaller children all patients had double lumen endotracheal intubation. All patients had conventional posterolateral thoracotomy. Stump closure was done in 2 layers with continuous prolene 1 & 2/0. Reinforcement of stump with intercostals muscle flap or pleural flap was done in all cases. Single chest drain was placed for first 24 hours in all cases. ICU care given post operatively and chest physiotherapy in the form of incentive spirometry, breathing exercises and bronchodilators was done in all cases pre and postoperatively. Specimen sent for histopathology and follow up was done in all cases. Results: Out of 320 cases 190 were male and 130 female, age range from 4 months to 74 years with a mean age of 32.5 years. Clinical presentation was recurrent chest infection with copious amount of foul smelly sputum in 128 cases (40%), recurrent hemoptysis in 176 cases (55%) and chest pain in 16 cases (5%).Tuberculosis was present in 198 cases (61.9%), bronchiectasis in 107(33.4%) and pulmonary Aspergilloma in 15 cases (4.7%). Left sided pneumonectomy was performed in 215 cases whereas right sided was performed in 105 cases. Mortality was 11/320(3.43%) and morbidity was 36/320(11.25%). Out of 36 cases Bronchopleural fistula was seen in 11 cases, post pneumonectomy empyema 08 cases and wound infection in 17 cases. Conclusion: Pneumonectomy is the most effective treatment in symptomatic patients with destroyed lung. We recommend reinforcement of stump with intercostals muscle flap or pleural flap, meticulous closure, early pre and post operative triflow exercises for better outcome
Keywords: pneumonectomy, benign lung disease, Bronchopleural fistula, post pneumonectomy empyema.